Scientific production on instruments adapted to native languages in the Peruvian context - Phoco-Arhuiri, Ruth M.; Figueroa-Quiñones, Joel; Cjuno, Julio (Frontiers in Psychology, 2025)
ObjectiveTo describe the scientific output on instruments adapted to Indigenous languages in Peru.MethodsA narrative review was conducted based on a search in Scopus, SciELO, PubMed, and LILACS using search terms related to psychometric properties, Peru, and Indigenous languages, refining the search by title, abstract, and keywords. The search was conducted in January 2025, yielding 9 studies in Scopus, 4 in SciELO, 28 in PubMed, and 10 in LILACS. After removing duplicates and excluding studies that did not meet the inclusion criteria, a final sample of *n* = 6 studies was obtained.ResultsThe instruments adapted to certain Quechua varieties assessed depression, anxiety, general mental health, overall well-being, and life satisfaction. Five out of six studies were conducted with bilingual adult populations. A smaller number of items corresponded to smaller sample sizes (e.g., *n* = 186 as the minimum for 5 items). The studies examined sources of validity including internal structure, content, criterion-related evidence, and measurement invariance. For reliability, they used classical Alpha coefficients and McDonald’s Omega.ConclusionFew studies were found on the adaptation of psychometric instruments to certain Quechua varieties. The instruments addressed the assessment of depression, anxiety, general well-being, life satisfaction, and overall mental health. University authorities in Peru could foster psychometric research initiatives within Indigenous communities.